2018
DOI: 10.1128/mbio.02435-17
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Functional Gene Diversity Predicts Groundwater Contamination and Ecosystem Functioning

Abstract: Contamination from anthropogenic activities has significantly impacted Earth’s biosphere. However, knowledge about how environmental contamination affects the biodiversity of groundwater microbiomes and ecosystem functioning remains very limited. Here, we used a comprehensive functional gene array to analyze groundwater microbiomes from 69 wells at the Oak Ridge Field Research Center (Oak Ridge, TN), representing a wide pH range and uranium, nitrate, and other contaminants. We hypothesized that the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 65 publications
1
37
1
Order By: Relevance
“…This is seen in the less-contaminated areas, Wadi Hovav and Downstream; at times low diversity indices occur in boreholes with low contaminant load, such as RH26, and vice versa, while high diversity indices occur in boreholes with relatively high contaminant load, such as S3. A recent report on the functional diversity of the microbial community in nitrate and uranium-polluted groundwater had suggested that diversity decreases with increasing pollution [47]. However, as in our study, the relationship between contaminates load (uranium) and functional genes richness was insignificant.…”
Section: Pollution Extent Affects Community Diversitycontrasting
confidence: 62%
“…This is seen in the less-contaminated areas, Wadi Hovav and Downstream; at times low diversity indices occur in boreholes with low contaminant load, such as RH26, and vice versa, while high diversity indices occur in boreholes with relatively high contaminant load, such as S3. A recent report on the functional diversity of the microbial community in nitrate and uranium-polluted groundwater had suggested that diversity decreases with increasing pollution [47]. However, as in our study, the relationship between contaminates load (uranium) and functional genes richness was insignificant.…”
Section: Pollution Extent Affects Community Diversitycontrasting
confidence: 62%
“…Recent studies have tried to describe microbial communities in groundwater ecosystems in situ, or in microcosm experiments that simulated environmental conditions (1320). Results from high-throughput sequencing of 16S rRNA gene amplicons show that a large number of microorganisms in groundwaters cannot be classified even on class or phylum level (13, 17), which largely precludes assumptions about their biodegradation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Results from high-throughput sequencing of 16S rRNA gene amplicons show that a large number of microorganisms in groundwaters cannot be classified even on class or phylum level (13, 17), which largely precludes assumptions about their biodegradation potential. Whereas some studies examined the correlations among microbial community, pollutant abundance, and geochemical parameters (13, 1820), these datasets did not consider stabilities in microbial community and redox conditions within the aquifer, over time and spatially. Considering the diversity of electron acceptors, dissolved organic carbon (DOC) as electron donor, and low nutrient concentrations in groundwater, long-term repeated sampling of microbial communities in a variety of groundwater compositions at a fixed set of locations and depths is required to make conclusions about MP natural attenuation distributions over aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has shown that the microbial species composition, derived from meta-genomic sequencing, may be useful for determining the presence of particular contaminants [6]. Our results suggest that further incorporation of species-specific gene expression patterns can likely improve the accuracy of such methods.…”
Section: Discussionmentioning
confidence: 68%
“…By contrast, prior work has shown that the natural species composition of an environment may be sufficient to serve as a rapid and low-cost biosensor to indicate the presence of various contaminants according to the species abundances identified via meta-genomic sequencing [69]. However, many bacterial species within a community are generalists that are capable of thriving in diverse environments and must therefore sense and respond to various environmental signals [10].…”
Section: Introductionmentioning
confidence: 99%